Influence of nutrition literacy on college-age population’s dietary behavior - Song, Xiaofei (Kansas State University, 2014)
Background: With the growing concern of obesity in the United States, food, as the main source of energy and nutrition has become an issue of research interest. Though the Nutrition Labeling and Education Act of 1990 (NLEA) requires nutrition information to be made available for customers in order to guide their dietary choices and intake, obesity rate has increased significantly in the past 20 years. This study examined how nutrition literacy affects college-age population’s reading nutrition labels, and how motivation of label reading associated with predictors of the label reading behavior. Method: An online, self-administered questionnaire was conducted among a randomized sample of 171 students from a Mid-Western university. The questionnaire was structured with key variables derived from the Theory of Planned Behavior (TPB) and the Elaboration Likelihood Model (ELM); such as attitude to make food choices based on reading nutrition labels. Levels of nutrition literacy were measured by questions derived from a nutrition labels survey. Data analysis was conducted with Pearson’s correlation and analysis of variance (ANOVA). Results: Majority of the college student respondents in this study had adequate nutrition literacy. Though no significance was revealed from the correlation between nutrition literacy and the dependent variables due to the limit variance in nutrition literacy data, this study found that individual’s motivation to read nutrition label and attitude towards reading nutrition label are positively related. Results also showed that individuals with higher motivation to read nutrition labels have better perceived behavioral control of reading nutrition labels. Conclusion: Participants in this study, as an emerging adulthood population with college-level education, revealed adequate nutrition literacy in general. It can also be concluded that improvement in attitude towards certain behavior relates to development in motivation and perception-based involvement.
Keywords: Health Communication; Communication (0459)